Identification of the Juvenile Wood Transition Age and of Some Growth Characteristics in Plantation vs. Native Populations of Cuban Pinus caribaea M. var. caribaea B&G - Ana Gertrudis Trocones Boggiano; Lidia Gurau; Mihaela Porojan; Mariana Domnica Stanciu (BioResources, 2025)
Identifying the transition age between juvenile and mature wood is key for designing more efficient silvicultural strategies and optimizing timber exploitation.  The objective of this study was to identify the juvenile wood transition age and analyze certain growth characteristics of Cuban Pinus caribaea M. var. caribaea B&G by comparing plantation and native populations. Radial variations in growth ring width, latewood proportion, and ultrasonic longitudinal speed were examined to identify the delimitation age from juvenile to mature wood. Visual assessment and statistical analyses, including segmented regression and k-means clustering, were applied. The findings indicated that juvenile wood is formed within the first 5 to 9 years, while mature wood develops after 21 to 26 years. Plantation trees exhibited higher variability and a wider juvenile wood zone (60 mm from the pith) than native trees (43 mm). The mean growth ring in the mature wood was 3.14 mm in native and 3.67 mm in plantation. The latewood proportion stabilized above 50% beyond the transition age, confirming the shift to mature wood, trees from native population developing 22% more latewood than trees from plantation. The ultrasonic speed pattern was similar between populations, validating its use as an indirect indicator of wood maturation.